Neglected reactive arthritis complicated by bilateral hip and temporomandibular joints ankylosis after a suspected tetanus infection: a case report - Mohamed A. Mahran; Ahmed A. Khalifa; Mohamed Eslam Elsherif; Omar Refai (SpringerOpen, 2021)
Abstract Background Reactive arthritis had been reported to occur after various vaccinations, including the tetanus toxoid vaccine; here, we report a case of ankylosing arthropathy suggested to be a complication of missed neglected reactive arthritis after tetanus infection. Case presentation A healthy 20-year-old woman presented with subtrochanteric right femoral fracture; imaging studies showed bilateral ankylosed hip, kyphoscoliosis, bilateral fused temporomandibular joints, and normal sacroiliac joints bilaterally. Laboratory investigations for a rheumatic or autoimmune disease were all within normal ranges. Detailed history revealed admission of the patient to an ICU unit (1 year before the trauma) for a month as she was diagnosed as having tetanus infection, after which she was unable to walk or feed herself. At the final follow-up, the patient started walking with a moderate limb after having a series of surgeries including femoral fracture fixation, temporomandibular joint excision arthroplasty, and bilateral total hip arthroplasty. Conclusion Unusual complications after tetanus infection can occur in the form of joint ankylosis, which could be presented after prolonged immobilization possibly due to improper management of reactive arthritis.